PENTINGNYA IMPLEMENTASI WAWASAN KEBANGSAAN DALAM MENCEGAH DAN MENGATASI TANTANGAN KEBERAGAMAN DI INDONESIA - Sihombing, Daniel Romi; Sihombing, Denissa Angela (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDC, 2025)
Diversity in Indonesia is both a gift and a threat. Diversity can create opportunities for disunity. Especially if coupled with the arrival of external influences due to globalization. This can be overcome and prevented through the implementation of nationalistic insight. This research aims to provide a solidification of understanding related to nationalistic insight, so that it can be implemented in the life of the nation and state. This research uses literature study method, by collecting literature from various sources.